Multivariate Garch modelling for european banking and portuguese firms - Teixeira, Joana Isabel Duarte Mouro Franco (2015)
In the present work, an empirical study is made in two different periods of time (02/01/2006 – 11/04/2014 and 01/08/2007 – 01/07/2010), about the time structure of the daily return rates correlations in the European Bank Sector and Portuguese firms with different market capitalization. For this purpose four different groups were built (bank sector, small, medium and large market capitalization) to inquire if the return rates correlations are stable and if they have an asymmetrical behavior. Using the two periods of time for the return rates of the groups built, the results obtained allow to conclude that most return rates have the statistical properties of financial series and that conditional variance models are mostly asymmetrical. Finally, the conditional and unconditional analyses of correlations shows that these are not very strong when including the whole period of analysis. However, the Financial Crisis made the correlations increase greatly due to instability and financial contagion. These conclusions suggest that the benefits of an investor adopting a size diversification strategy in the Portuguese firms and European bank sector are low.